Pengaruh Motivasi dan Budaya Organisasi Terhadap Kinerja Pegawai di Pusat Pelayanan Teknologi Masa Pandemi Covid-19 - Lukito Eminiyati; Derinta Entas (Pusat Riset dan Inovasi Nasional, 2025)
The pandemic has caused significant changes in various aspects of life, including the way of working and interaction patterns in organizations. Motivation and organizational culture play an important role in influencing employee performance, especially in dealing with uncertainty and rapid change. This study uses a quantitative approach with a survey method and data analysis using multiple linear regression. The research sample consisted of 52 employees at the Technology Service Center selected randomly. Data were collected through a questionnaire that measured three main variables: motivation, organizational culture, and employee performance. The results show that motivation has a positive and significant effect on employee performance, which means that the higher the motivation of employees, the better their performance. In addition, organizational culture has been shown to have a positive effect on employee performance. Organizations with a culture that supports effective communication, collaboration, and adaptation to change are able to improve employee performance even in difficult conditions due to the pandemic. The importance of motivation and an adaptive organizational culture in maintaining and improving employee performance, especially in facing challenging times such as the Covid-19 pandemic.